Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/elps.200900145
|View full text |Cite
|
Sign up to set email alerts
|

Genetic categorization of Echinococcus granulosus from humans and herbivorous hosts in Iran using an integrated mutation scanning‐phylogenetic approach

Abstract: In the present study, we have extended earlier taxonomic, biochemical and experimental investigations to characterize Echinococcus granulosus from various hosts in Iran utilizing DNA regions (designated pcox1 and pnad1) within the cytochrome c oxidase subunit 1 and NADH dehydrogenase 1 mitochondrial genes, respectively. An emphasis was placed on the characterization of E. granulosus isolates (cyst material) from humans, sheep, goats, cattle and camels, and on assessing their genetic relationships. PCR-based SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 34 publications
(56 reference statements)
9
59
2
1
Order By: Relevance
“…Previous studies have indicated the presence of the G6 genotype in different hosts such as sheep, goats, cattle, camels, and humans in Iran. 28,29,32,40,56 However, the high prevalence of the G6 genotype in this study is not in accordance with previous human CE studies in Iran (Table 1), because most of these studies indicated the G1 genotype as the only genotype found in humans. However, the sample sizes used within some of the previously mentioned studies were very low.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Previous studies have indicated the presence of the G6 genotype in different hosts such as sheep, goats, cattle, camels, and humans in Iran. 28,29,32,40,56 However, the high prevalence of the G6 genotype in this study is not in accordance with previous human CE studies in Iran (Table 1), because most of these studies indicated the G1 genotype as the only genotype found in humans. However, the sample sizes used within some of the previously mentioned studies were very low.…”
Section: Discussioncontrasting
confidence: 94%
“…1,26 Several molecular epidemiological studies have been performed on E. granulosus isolates in Iran using sequence data of mitochondrial and nuclear genes. Overall, four different genotypes of E. granulosus (genotype G1, G3, and G6) have been reported from different livestock [27][28][29][30][31][32][33][34][35][36] and dogs (genotype G1, G2, and G3) 37 from Iran. To date, only a few human isolates of E. granulosus have been genetically characterized in Iran that indicated G1, G3, and G6 genotypes ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, the pig strain G7 was reported in one human isolate and two isolates from sheep (13). Our results are consistent with the data obtained by other authors who used different techniques, such as PCR-RFLP (15,(32)(33)(34)(35)(36)(37) and SSCP (17,22,(38)(39)(40) analyses for the genotyping of E. granulosus. In addition, we examined 13 isolates of E. granulosus from different intermediate hosts using sequence analysis of the mitochondrial ND1 and CO1 genes.…”
Section: Discussionsupporting
confidence: 92%
“…The mitochondrial ND1 region was amplified by PCR using MS1 and MS2 primers (22 of PCRs, positive [G1: EU503084 (20), and G6-G10 complex: GU951511 (18)] and negative (no-DNA) controls were included. Four microliters of each PCR products were mixed with 12 µl of denaturating buffer.…”
Section: Pcr-sscp Analysismentioning
confidence: 99%
See 1 more Smart Citation